If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + 5) = (11x + -25) Reorder the terms: (5 + 9x) = (11x + -25) Remove parenthesis around (5 + 9x) 5 + 9x = (11x + -25) Reorder the terms: 5 + 9x = (-25 + 11x) Remove parenthesis around (-25 + 11x) 5 + 9x = -25 + 11x Solving 5 + 9x = -25 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 5 + 9x + -11x = -25 + 11x + -11x Combine like terms: 9x + -11x = -2x 5 + -2x = -25 + 11x + -11x Combine like terms: 11x + -11x = 0 5 + -2x = -25 + 0 5 + -2x = -25 Add '-5' to each side of the equation. 5 + -5 + -2x = -25 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = -25 + -5 -2x = -25 + -5 Combine like terms: -25 + -5 = -30 -2x = -30 Divide each side by '-2'. x = 15 Simplifying x = 15
| 10000*3.12= | | 88=(5+2y)*y | | 3(2b-a)-(2a-b)= | | (X^2+2x+40)=(x^2)-x+190 | | m(x)=x^5-10x^4+25x^3 | | 8(x+y)+3(x+y)= | | 4a+7a=9 | | 4.5x-1.8=3.2x+0.8 | | X^2=3+x | | z+2.6z-5.5=(z-0.3) | | 6(x-y)-3(3x+y)= | | -4.2-6y-4.7-2y=-7y-1.3 | | 4x-12=-48 | | 4(y-7x)-y= | | 5z=18z | | 5z=8z | | 10-(2z-1)=1-3z | | (4x-3)(x-5)=(-11x+1)(3x-2) | | 4x^2-56x+184=0 | | 12x-3y+x+2y= | | 7+f=1+4f | | 4x^2-40x+100=44 | | 7f=1+4f | | 2x^2+4x=3 | | 4*x-3=2x*-3-2 | | 3*2x-5=2x-7 | | 2x*2+3x=2*4x-3 | | 10xy*4y= | | 2*4-5x=7-3x-4 | | 2x+x=-20x | | 2x+3-4-3x=x-2+2x | | 3(2y-4)=2(1-5y)+11 |